2004
DOI: 10.1021/ol048789w
|View full text |Cite
|
Sign up to set email alerts
|

A Remarkably Efficient Coupling of Acid Chlorides with Alkynes in Water

Abstract: [reaction: see text] A highly effective direct coupling of acid chloride with terminal alkynes catalyzed by PdCl(2)(PPh(3))(2)/CuI together with a catalytic amount of sodium lauryl sulfate as the surfactant and K(2)CO(3) as the base provided ynones in high yields in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(57 citation statements)
references
References 10 publications
0
57
0
Order By: Relevance
“…(71)]. [142] In addition, other types of [3 + 2] 1,3-dipolar cycloadditions in water have been reported recently.…”
Section: A C H T U N G T R E N N U N G [3+2] 13-dipolar Cyclizationmentioning
confidence: 99%
See 1 more Smart Citation
“…(71)]. [142] In addition, other types of [3 + 2] 1,3-dipolar cycloadditions in water have been reported recently.…”
Section: A C H T U N G T R E N N U N G [3+2] 13-dipolar Cyclizationmentioning
confidence: 99%
“…(21)]. [71] No desired product was detected when either Cu(I) alone or Pd(II) alone was used as the catalyst. The use of surfactant was also necessary for the success of this transformation, possibly by temporarily stabilizing the acid chloride.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Since it was reported that the Diels-Alder reaction can be accelerated by using water as a solvent, instead of organic solvents, [4] considerable attention has been directed toward the development of organic reactions in water-even among water-sensitive compounds. [5] Sharpless et al reported a remarkable phenomenon: they found that the reaction was substantially accelerated when insoluble reactants were stirred in an aqueous suspension; this was denoted as the "on water" condition. [6] For the nucleophilic opening of epoxide in an aqueous suspension, the researchers observed that the reaction was completed overnight after heating at 50 8C, while the reaction in ethanol or under neat conditions required approximately three days to reach completion.…”
mentioning
confidence: 99%
“…Chen and Li (150) reported an efficient coupling of acid chloride (43) with terminal alkynes (44) using PdCl 2 (PPh 3 )/CuI as co-catalysts and a catalytic amount of surfactant/phase-transfer reagent under basic conditions in water (Scheme 16). Various aryl acid chlorides were coupled with alkyl and arylalkynes with high yields (51Á99%).…”
Section: Coupling Of Acid Chloride With Terminal Alkynesmentioning
confidence: 99%